PENGARUH BUDAYA SEKOLAH TERHADAP KARAKTER RELIGIUS SISWA SMP NEGERI 4 PEKANBARU - Yulliyani, Eva Yulliyani Eva; Erlinda, Sri Erlinda Sri; ', Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Basiclly education can take place in three places, namely family, community and school. School is the venue for teaching and learning. Learning and teaching are not only meant as knowledge transfer activities from teacher to student. Various activities such as how to familiarize all citizens of school discipline and adhere to the rules that apply in school, mutual respect, familiarize clean and healthy life and has the spirit of fair competition and the like is a habit that must be grown in the school everyday. The activities related to character education already widely implemented are reflected in the Vision of SMPN 4 Pekanbaru namely a writer doing research. The aim of this study is to investigate to find out influence school culture to the religious character of students in SMP Negeri 4 Pekanbaru. Population of this research are all students of SMP Negeri 4 Pekanbaru the school year 2014/2015, amounting to 897 students and the sample was taken as much as 15% of the total population to 135 respondents. The method use disdescriptive quantitative. Data collection instruments, namely a questionnaire consisting of 13 questions about the influence of school culture (variable X) and 23 questions abou the religious character of the student(Y). Data were analyzed using linear regression. With a series of simple regression test between the variables X and Y, obtained F count ttabel 3,92 obtained 6.34 and the value of the distribution list F table study with N = 135, at significance level of 5%, thus F count> F table, or 6,34>3.92. So the hypothesis that there is a cultural influence on the formation of the character of a religious school students in SMPN 4 Pekanbaru accepted. Key words : Schoolculture, Religious Character